Alegoría y cultura histórica franciscana en los azulejos portugueses del Convento de San Antonio de Paraíba (Brasil, siglo XVIII) - Oliveira, Carla Mary S. (Pontificia Universidad Católica del Perú, 2025)
The tile strip in the church of the Saint Anthony Convent in Paraíba, created in the 1730s, narrates the Joseph of Egypt’s saga in a continuous storyboard. This decoration reinforces the concept of a saintly life as an exemplary model, employing religious imagery as a guide for behavior, aligning with the Baroque historical culture rooted in Trento. This study delves into the allegorical and symbolic implications of the chosen theme and its treatment in the Paraíba Franciscan convent’s decoration.

La franja de azulejos en la iglesia del Convento de San Antonio en Paraíba, producida en la década de 1730, representa la saga de José de Egipto en una narrativa continua. Esta decoración refuerza la idea de una vida santa como ejemplo, utilizando imágenes religiosas como modelo de conducta, en sintonía con la cultura histórica barroca arraigada en Trento. Se pretende analizar las alegorías y las implicaciones simbólicas del tema elegido y su tratamiento en la decoración del convento franciscano.
Allegory and historical Franciscan culture in the Portuguese tiles of the Convent of San Antonio de Paraíba (Brazil, 18th century)
Keywords: Portuguese tiles; Kunstwollen; Franciscans; Historical culture; Seraphic pedagogy; Brazil; 18th century; Azulejos portugueses; Kunstwollen; Franciscanos; Cultura Histórica; Pedagogía Seráfica; Brasil; Siglo XVIII; https://purl.org/pe-repo/ocde/ford#6.00.00